EVALUASI KINERJA AKUNTAN PUBLIK: SKEPTISME PROFESIONAL DAN OUTCOME EFFECT (SEBUAH STUDI EKSPERIMENTAL) - Sari, Gisilowati Dian Purnama; Juliarto, Agung; Raharja, Raharja (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
Professional skepticism is a behavior that it is although encouraged by the profession does not always produce the same outcome (e.g., sometimes it leads to the identification of a misstatement and other times it may not). Highly skeptical auditors increase the likelihood that material misstatements are detected, which is important in promoting investor confidence and global financial stability. However, exercising skepticism may also come at a cost (e.g., budget overruns and potential conflicts with management). The failure to identify a material misstatement in the financial statements may result in restatements. Research on outcome effects suggests that auditor’s performance evaluation may be influenced more by the outcome of their skeptical behavior (i.e., whether or not a misstatement is found) than by whether they engaged in the appropriate level of skeptical behavior. This study aims to obtain new empirical evidence whether there is a difference between the auditor’s performance evaluation when a misstatement is found than when no misstatement is found. These studies further examine whether consultation during the process of exercising skepticism can alleviate the outcome effect bias.This is a experimental that research for a causal relationship between the dependent variabel and independent variable. Respondents in this study is the auditor who has experience doing supervision. Repondents were gethered in the seminar organized by IAPI and PPPK. Seminar was held on 2016 may 30th, in Semarang Quest Hotel. Testing of this reserch using indepent sample t-test and two way ANOVA.Finding of first experiment finds that the outcome of an investigation will affect auditors’ performance evaluations. There are significant differences of performance evaluations between staff who do not identify a misstatement versus staff who do identify a misstatement. This reserach also examine whether responses are significantly higher when a misstatement is found than when no misstatement is found. Futhermor result of this study reveal that consultation with the superior during the process of exercising skepticism effectively mitigate the outcome effects in auditor evaluations. The result of this study show that the evaluators did not effected the outcome effect in auditor’s performance evaluation.